Killings in context: an analysis of the news framing of femicide - Bouzerdan, Camelia (Human rights review, 2018)
While attacks against members of the LGBT community are increasingly covered as hate crimes and are widely viewed as a form of repression, attacks on women are almost never covered as violations of human rights. We propose that until violence against women is recognized as a form of repression and a threat to the physical security of women, we cannot expect much to be done to prevent it. We posit that policies aimed at preventing violence against women are unlikely to come about unless this abstract concept is connected, through a connection frame, to concrete crimes against women. We conducted a framing analysis of news coverage of all confirmed femicides in Massachusetts in 2013 and find that while journalists have the potential to draw these connection frames, they seldom put these killings in the context of violations of women’s rights.